The Process of Iranian Cultural Identity Formation in Interaction with Islam: A Historical Review - Taheri, Ahmad Reza; Shahrokhi, Seyed Alaeddin; Salah, Mehdi; Razavi, Seyed Abolfazl (ISTORIA : Jurnal Pendidikan dan Ilmu Sejarah, 2023)
This paper is inspired by the hypothesis of the "Undeniable position of divine religions in the identification of societies and the cultural essence of Islam", discussing the following, respectively: Iranian cultural identity in classical sources, important axis of this identity on the eve of the arrival of Islam, Iran's accession to the Islamic caliphate without adopting the Arabic identity, prominent identity indicators of Islamic culture, formation of Iranian Islamic identity and factors responsible for the cohesion of the Iranian Islamic identity. The present paper suggests that the elements of the identity of the ancient Iranian culture, which were not in conflict with the Islam, were preserved, and what was not in harmony changed.